Survey of Rasch Model Analysis of Mathematical Literacy Abilities of Senior High School Students - Widyaningrum, Azzahra; Lutfiyana, Riza Dwi; Faradillah, Ayu; Miatun, Asih (Pattimura University, 2024)
Mathematical literacy skills are needed in everyday life, but the mathematical literacy skills of students in schools show that Indonesian students are very low in the field of mathematical literacy. Therefore, this study aims to determine the Rasch model analysis survey of mathematical literacy skills of senior high school students. This study uses quantitative research methods with a survey approach and uses the Rasch model as a measurement. The subjects studied were 100 students consisting of grades X and XI of high schools in Bekasi city. Furthermore, the results of this study indicate that there is 1 out of 8 items that are misfit and for the provisional calculation of reliability is 0.42, so it is declared not reliable and for the DIF test results there is only one item that is biased.